Secondary pupils' tendencies towards pedagogical sports activity according to the gender variable. Field study conducted on the secondary schools of the state of Tissemsilt - كحلي , أحمد; ربوح , صالح (Journal of Sport Science Technology and Physical Activities, 2024)
This study aims to identify attitudes of secondary school students towards practicing educational physical activity , Where the researchers used the approach method sample of 378 students randomly selected to collect data about this phenomenon we used the Kenyon scale.After collecting the data and processing istatistically It turns out that:- Students’ towards practicing educational sports activities were positive.- There are statistically significant differences between the sexes in theattitude towards educational sports activity.On basis, the study recommended the necessity of encouraging sportspractice, especially for females and educating about its importance to the soul and body